Tantangan Birokrasi dalam Implementasi Program Bantuan Sosial untuk Penyandang Disabilitas di DKI Jakarta - Alboin Cristoveri Samosir; Sari Viciawati Machdum (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This research aims to understand the implementation process of the Jakarta Disability Card (KPDJ) by analyzing the challenges that exist in the bureaucratic structure of the program. As part of the social policy to fulfill the rights of persons with disabilities, KPDJ is a social cushion for underprivileged persons with disabilities. Qualitative research with an interpretive paradigm was conducted by interviewing actors involved in program implementation and beneficiaries. The policy implementation framework of George C. Edwards III (1980) became the basis for analyzing this research. The results show how the KPDJ implementation process works to improve the lives of people with disabilities. Using a qualitative approach through document study, observation, and in-depth interviews, this research found various challenges in the bureaucratic structure that are closely related to resources and communication. Standard operating procedures (SOPs) face challenges from uniformity with other social assistance programs, non-standardized processing times, minimal resource availability, and stagnation of innovation due to the absence of monitoring and evaluation. Fragmentation in the division of authority also faces challenges from data integration and the organization of supporting facilities. This situation creates a distance between inclusion-oriented policy design and procedural administrative practices.